A Randomized, Controlled, Parallel-Group, Trial on the Effects of Melatonin on Fatigue Associated with Breast Cancer and Its Adjuvant Treatments. (February 2021) - Sedighi Pashaki, Abdolazim; Mohammadian, Kamal; Afshar, Saeid; Gholami, Mohammad Hadi; Moradi, Abbas; Javadinia, Seyed Alireza; Keshtpour Amlashi, Zahra
Objective: Fatigue associated with malignant conditions and their treatments is a disabling condition. This trial assessed the anti-fatigue effects of melatonin coadministration during adjuvant treatment of patients with the breast cancer. Material and Methods: Patients with breast cancer were randomly assigned to receive melatonin or placebo during adjuvant chemotherapy and radiotherapy. Thirty-seven patients were randomly enrolled in each group. The mean ages of patients in the intervention and control groups were 50.47 ± 10.79 and 46.05 ± 10.55 years, respectively ( P = .223). The intervention group received oral melatonin (18 mg/day) from 1 week before until 1 month after the adjuvant radiotherapy. The level of fatigue was assessed before and after intervention using Brief Fatigue Inventory (BFI) in both groups. To analyze data, the Student's t -test and the Chi-square test were used at a significance level of P ≤ .05. Results: The BFI score was similar before the intervention in both groups, however, after the intervention, it was significantly lower in the melatonin group ( P < .001). Moreover, the frequency of severe fatigue in the melatonin group was significantly lower than in the placebo group after intervention (42.1% vs 83.3%, P < .001). Conclusion: Coadministration of melatonin during adjuvant chemotherapy and radiotherapy of women with breast cancer decreased the levels of fatigue associated with the malignant condition and its treatments.